The clinical application and anatomical analysis of proximal peroneal artery perforator in free fibula flap based on CTA - Yitong Zhao; Danwei Xiang; Lina Song; Zhujiajun Cui; Xingwu Zheng; Tianyu Zhang; Huihui Yang; Yongzhen Fu; Qilin Liu (BMC Oral Health)
Abstract Background The vascularized free fibular flap is increasingly recognized as the standard technique for the repair of complex soft tissue and hard tissue defects in oral and maxillofacial surgery. Conventionally, the vascular supply to the skin island is derived from the distal perforators of the peroneal artery. However, complications may arise if these distal perforators are either absent or damaged during surgical procedures, highlighting the necessity to employ the proximal peroneal perforators as an alternative. This study aims to investigate the anatomical characteristics—including the presence, distribution, and origin—of proximal peroneal perforators through computed tomography angiography (CTA) prior to surgical intervention. A secondary objective is to confirm their viability when distal perforators are unavailable or when dual-skin paddles are needed. Methods A comprehensive review was conducted involving 50 patients who underwent CTA examinations. Three-dimensional reconstruction of DICOM data was utilized to document the presence, quantity, location, and variations of proximal perforators. Relative positions of the origin points were measured, and the distances from these points to the fibula were calculated. Additionally, 11 studies were included in which a proximal perforator was successfully used to prepare a free fibula chimeric myocutaneous flap for the reconstruction of maxillofacial defects. Results Among the 100 lower limbs evaluated, a successful identification rate of 98% for proximal perforators was achieved via CTA. Of those identified, 70% were found to originate from the fibular artery, 22% branched concurrently with it, and 8% emerged prior to the point of emergence of the fibular artery. Analysis through curve fitting indicated that the origin points of proximal perforators were predominantly located approximately 13.17 mm below the origin of the fibular artery, with their endpoints projecting about 123.9 mm below the fibular head. Conclusions The high prevalence of proximal peroneal perforators identified in this population, along with their relatively stable anatomical positions, suggests their significant surgical potential. In scenarios where the distal peroneal perforator is absent or suffers intraoperative injury, the proximal peroneal perforator can serve as a reliable alternative for preparing a free fibula osteal flap combined with a proximal peroneal perforator skin paddle.